1996
DOI: 10.1007/bf00241378
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual movement coordination in spastic hemiparesis

Abstract: A Fitts' task was used to examine whether the large movement asymmetry in subjects with spastic hemiparesis can be reduced or eliminated when both limbs are required to perform functionally equivalent tasks. Furthermore, it was determined whether any such benefit was expressed as mutual accommodation, or whether one hand "slaves" the other. Finally, the effect of increased task constraints on the magnitude of the asymmetry was considered. A group of ten students served as controls. Subjects had to grasp small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
39
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 23 publications
8
39
1
2
Order By: Relevance
“…Consistent with results from experiments that have examined bimanual reach and grasp tasks (Steenbergen et al, 1996;Sugden & Utley, 1995), it was found that for the first two cycles of a bimanual circular movement, children with SHCP were able to maintain a similar mean temporal coordination pattern (i.e., mean CRP and movement time) compared with an age-matched control group. However, children with SHCP showed greater variability of the coordination pattern (i.e., SD CRP) compared with the TD children, and exhibited increased normalized jerk in the more impaired arm compared with the less impaired arm.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Consistent with results from experiments that have examined bimanual reach and grasp tasks (Steenbergen et al, 1996;Sugden & Utley, 1995), it was found that for the first two cycles of a bimanual circular movement, children with SHCP were able to maintain a similar mean temporal coordination pattern (i.e., mean CRP and movement time) compared with an age-matched control group. However, children with SHCP showed greater variability of the coordination pattern (i.e., SD CRP) compared with the TD children, and exhibited increased normalized jerk in the more impaired arm compared with the less impaired arm.…”
Section: Discussionsupporting
confidence: 80%
“…Based on previous research, it was expected that both groups would be able to exhibit a symmetrical coordination pattern (Volman et al, 2002;Robertson, 2001;Utley & Sugden, 1998;Steenbergen, Hulstijn, De Vries, & Berger, 1996;Sugden & Utley, 1995). However, the children with SHCP were expected to perform the movement with more variability between the arms than the TD control population (Volman et al, 2002;Steenbergen et al, 1996).…”
mentioning
confidence: 99%
“…Corroborating this assumption is the present finding of a strong trend for larger absolute timing differences between peak velocity and peak aperture at the contra-lesional side. Indeed, it was shown previously that attention is almost exclusively focused on the contra-lesional hand during bimanual movement performance in this group (Steenbergen et al 1996).…”
Section: Discussionsupporting
confidence: 50%
“…Children with hemiplegic CP also have impaired bimanual coordination above and beyond their unilateral upper extremity impairments (9,(25)(26)(27)(28). Bimanual coordination impairments may underlie some of the functional limitations these children experience in activities such as dressing, eating, and playing sports.…”
mentioning
confidence: 99%